KEYAKINAN-KEYAKINAN UTAMA MAHASISWA PENGGUNA MOBIL KE KAMPUS - Setiawan, Rudy (Jurnal Transportasi, 2012)
The most common daily trip for students is the commute to and from campus. Students tend to choose car when commuting. This preference has resulted in a number of negative effects. Therefore it is necessary to investigate the psychological factors influencing studentsâ car use behavior. The popular theory of plannedbehavior (TPB) was successfully applied by different authors to explain peopleâs travel mode choices.According to TPB, intentions are the closest antecedents of behavior, and intentions were resulted fromattitudes, subjective norms, and perceived behavioral control. TPB assumes that these components are in turndetermined by salient beliefs for each component and evaluations of those beliefs.This study elicit studentsâsalient beliefs in relation to car commuting, that could be used to construct a full TPB questionnaire. Thisquestionnaire could then be used to investigate student car commuting behavioural intention. A sample ofstudents from four different university, with a sample size of 200 people, completed questionnaires with eightopen-ended questions eliciting beliefs concerning car use. The results indicated that the most frequentlymentioned salient beliefs related to behavioral beliefs are comfort, security, flexibility, prestige, parkingfacilities, congestion, and travel cost. Meanwhile, those related to normative beliefs are parents,boyfriend/girlfriend, and friend, and those related to control beliefs are parents, car availability, number ofcar owned, carâs technical problem, congestion, and travel cost.Keywords: theory of planned behavior, studentâs salient beliefs, car use for commuting.